Desejabilidade social e avaliação da empatia em testes de autorrelato: estudo de uma nova escala - Toniato, Iuri Livramento (Universidade Federal de São Carlos, 2025)
The assessment of empathy, an important social skill, often relies on self-report tests, which are vulnerable to social desirability (SD). This bias, characterized by individuals' tendency to respond in socially acceptable ways, can distort responses and compromise the accuracy of results, especially in empathy measures. This study examined the impact of SD on the assessment of empathy using the Online Empathy Questionnaire (QoE) and tested a new scale format (QoE-2B), focused on the frequency of empathic behaviors, aiming to minimize this bias. Participants included 1,005 individuals, who responded to versions of the traditional Likert scale (QoE-2A) or the newly proposed scale (QoE-2B), as well as the Marlowe-Crowne Social Desirability Scale (EDSMC-20) and the Big Five Inventory 2 (BFI-2-S). The results indicated that the QoE-2A showed a positive and significant correlation with the DS (r=0.35, p<0.01), while the QoE-2B showed no significant correlation with the DS (r=−0.01). Regarding personality traits, the QoE-2A correlated as expected with the BFI (e.g., Agreeableness, r=0.67), while the QoE-2B showed no significant correlation with any of the BFI dimensions. We conclude that the new scale format (QoE-2B) is promising in mitigating social desirability bias, offering a potentially more reliable assessment of empathy and raising questions about the different aspects that each format can measure.
Social desirability and empathy assessment in self-report tests: study of a new scale
Keywords: Desejabilidade social; Empatia; Testes de autorrelato; Avaliação psicologica; Personalidade; CIENCIAS HUMANAS::PSICOLOGIA::FUNDAMENTOS E MEDIDAS DA PSICOLOGIA::CONSTRUCAO E VALIDADE DE TESTES, ESCALAS E OUTRAS MEDIDAS PSICOLOGICAS